Iron wire phlebitis – a disease of underestimated significance. COVID-19 as a factor increasing the risk of Mondor's disease - Wiśniewska-Skomra, Joanna; Tylutka, Kinga; Hapon, Anna (Journal of Education, Health and Sport, 2023)
Mondor's Disease, also known as iron wire phlebitis, is a rare and self-limiting superficial vein thrombophlebitis that presents with a palpable cord-like induration beneath the skin. Others symptoms include: pain, swelling and redness of the affected area. It typically affects the vessels of the chest wall, less frequently the vessels of the penis or the upper limbs. The etiology of the disease is not fully understood, but it is known that it may be caused by local injuries or surgeries, and it may accompany cancer or infections. The diagnosis is based in most cases on an anamnesis and physical examination, confirmed by ultrasound. There are approximately 500 cases of this disease described in the literature. Iron wire phlebitis is a disease of underappreciated importance, raising awareness of this condition can facilitate the MD’ diagnosis and reduce unnecessary diagnostic procedures. A 36-year-old female patient detects a lump during breast self-examination. The lesion was located in the upper outer quadrant of the right breast. The ultrasound revealed dilated venous vessel with thrombosis, which led to diagnose Mondor's Disease. In this case the cause of increased coagulation may be ablation or COVID-19 infection. It is necessary to find the etiological factors predisposing to the disease, and extending the diagnosis to exclude other rheumatological, hematological and neoplastic diseases. The patient received low-molecular-weight heparin, heparin ointment, painkillers and anti-inflammatory drugs. After one week treatment, the change wasn’t palpable. Then, instead of LMWH, oral sulodexide was used for treatment. Thanks to awareness of this disease, it was possible to made an appropriate, quickly diagnosis and implement treatment, as well as reduce unnecessary medical procedures. The early diagnosis of MD can help to identify serious causes (for example breast cancer) at an early stage which will allow to treatment previously undetected changes.